Analysis of the COVID-19 situation in DIY and the efforts for adjustment of COVID-19 data between the central government and local governments - Lestari, Nining Puji (BKM Public Health and Community Medicine, 2021)
Abstract Objective: This study describes the COVID-19 situation in DIY and the efforts to adjust COVID-19 data between the local government and the central government. Methods: COVID-19 data was obtained from the Health Office of DIY Province with the main data source coming from the All Record TC-19 application. Results: there was a decrease in COVID-19 cases from the week before PPKM to October 18, 2021 (PPKM level 3), from an average of 272 cases per day to 88 cases per day. The average number of active cases also decreased from 30.93% to 2%. The death rate is still the same, namely 6 deaths per day. The distribution of the most COVID-19 cases was at the age of 21-30 years as much as 18.49%, and the lowest was found at the age of >81 years as much as 1.22%. The proportion of COVID-19 cases in DIY was more found in women by 52% than in men as much as 48%. As of October 20, 2021, the highest positive cases were in Bantul Regency at 31.98% of the total COVID-19 cases in DIY, and the lowest was in Kulon Progo Regency at 10.54%. Meanwhile, the highest recovery rate was in Kulon Progo Regency at 97.43% and the lowest was in Gunung Kidul Regency at 95.08%. The most COVID-19 case fatality rate was in Gunung Kidul Regency at 4.53% and the lowest was in Kulon Progo Regency at 2.18%. COVID-19 daily reporting is not fully real-time because the TC-19 all record application has not yet become a tool for executing COVID-19 reporting in districts in DIY while the central government uses all records as a tool for executing daily COVID-19 reporting. Conclusion: There was a decrease in the number of daily cases and active cases during the PPKM period in DIY, however, reporting was not fully real-time so efforts to create better COVID-19 data management becomes a challenge to be able to make COVID-19 reporting more reliable.